Two-Step Grafted F‑SiO2 Coating Self-Construction toward Mass-Produced Lithium–Metal Battery Separators with Optimal Porous Skeleton, Security, and Electrochemical Performances - Li, Dandan; Ding, Lei; Zhang, Sihang; Zhang, Yuanjie; Zhang, Peng-Fang; Du, Fanghui; Zhao, Shuyue; Zhang, Daoxin; Yang, Feng (ACS applied materials & interfaces, 2025)
High energy and power densities of lithium metal batteries (LMBs) attract continuing popular appeal, but extra requirements must be considered since disordered Li dendrites under violent Li fluxes pose challenges for flourishing LMB applications, especially for incompatible separators. In this research, a BPP@F-SiO2 composited separator is subtly prepared based on the two-step grafted SiO2 (F-SiO2) coating self-construction. F-SiO2 particles matched to lamellae sizes endow separators with centralized pore sizes. F-SiO2 coating self-construction on porous skeletons eliminates individual coating steps, which can simplify engineering equipment layouts and improve the actual manufacturing efficiency. Solvent-free and nonadhesive features avoid problems such as micropore blocking, thickness increase, and environmental pollution. Also, the F-SiO2 coating supplies extra Li+ for stabilizing the solid electrolyte interphase layer, homogenizing Li depositions, and acquiring remarkable electrochemical and battery performances for LMBs, which enable the BPP@F-SiO2 separator to be potentially applied in LMBs demanding sufficient security, high-capacity density, and fast charge technology. The proposed approach relies on current mainstream separator fabrication lines, which can achieve low-cost and large-scale production without developing extra production lines and lower practical application barriers of prospective LMBs.